Etyka zawodowa w rachunkowości - Garstka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2014)
Recently we have observed the high volatility and complexity of lawand business transactions, as well as the assumption of prepared valuationsand self-shaping principles in accounting. Greater independence in a changingenvironment increases the risk of unethical behaviour. There have been manycases of negative behaviour in accounting, known as a creative, aggressiveor fraudulent accounting. Responsibility for bankruptcy and financial failures waspinned on accounting, which shattered the reputation of the accountants concerned.Professional requirements for accountants are high and they have greatlyincreased, especially in the financial operations sector. However, it is expectedthat employees will also act ethically. Professionalism is associated in the sameway with professional competence and ethical standards. The Codeof Professional Ethics in Accounting introduces important ethical principles foraccountants. It is worth noticing how the principles refer to human traits, virtuesand considering whether to accept and obeying them as an act of conscience. Accountantsare facing ethical dilemmas that affect their private life.